Komunikasi Transendental Pada Upacara Tumpek Wariga - Ida Ayu Tary Puspa; Putu Agus Andita (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
Communication as a process of delivering massages from the communicator to the communication through media that produces effects, communication made by humans with God Using theinvisible can not be seen. Transcendental communication, which is communication that occurs between humans and their lord, also will berevealed the process of communication between humans and God in manifestation as the Sankara god who surround the trees in Tumpek Wariga. Basically Hindus really appreciate nature because it provides all the needs that humans need to continue their lives. On that basis, humans give tanks by carrying out the Tumpek Wariga ceremony which is also known as the growing otonan.Keywords : Trancendental communication, Tumpek Wariga.